New technology and increasing returns: The end of the antitrust century? - Kaushik Basu (Institute of Labor Economics (IZA), 2019)
The advance of digital technology is changing the nature of markets, enhancing the capacity of corporations to extract more consumers' surplus and lower the wages paid to workers. The rise of new technology has also diminished the efficacy of traditional laws to regulate firms and corporations. This is best illustrated by antitrust laws. With the new technology, there is greater returns to scale in production, and further, it is possible to have different components of the same final good be produced by different firms in faraway places. Unlike in earlier times the n firms in one industry, say the automobile industry, would all be producing cars, now the n firms in that industry produce n different parts of the product, thereby getting enormous returns to scale. Such markets are described as vertically serrated markets and their equilibria are characterized. Traditional antitrust law does not apply to these markets because the high returns to scale are natural and not artificially induced. This compels us to look for novel ways to regulate such markets. This paper discusses, in particular, laws that compel firms to have widely dispersed share holdings.
Keywords: F63; K21; L13; O33; 330; antitrust law; share distribution; technological advance; labor demand